The effect of employee professionalism, employee motivation and effectiveness of technology information on service population and civil registration on agam regency - Masnaidi B; Syamsir Syamsir; Dasman Lanin (Jurnal Aplikasi IPTEK Indonesia, 2018)
The study aimsto determine: 1) Howinfluence the professionalism of employee to the effectiveness of service in civil registry in Agam Regency. 2). How influence the work motivation to the effectiveness of service? 3) how influence the technology information to the effectiveness of service? 4) how much influence the professionalism, the work motivation and the information of technology employee to the effectiveness of service?The research method used is correlational qualitative method and 42 employees of civil registry as a population and 38 employes as sampel. The data analysis used is regression analysis and corelation.The finding sindicate that:1)Professionalisms of employee have a positive and significant effect on the effectiveness of service with a magnitude of 26,0%. 2)Work motivation has 36.6%positive and influence on the effectiveness service 3) the technology of information partially has 31.2%. positive andeffect on the effectivenessservice 4).Simultaneously significant influences employee professionalism, work motivation and information technology on the effectiveness service.at at 56.6%.